TOTOH GINGER COFFEE PRODUCTS IN INCREASING INCOME OF THE COMMUNITY OF KARANG ANYAR VILLAGE, KETAPANG DISTRICT, SAMPANG DISTRICT - Wahyudin, Ahmad; Handayani, Puji; Zagladi, Arief Noviarakhman (Multifinance, 2023)
The aim of this research is to find out the promotional strategy for Totoh ginger coffee products to increase the income of the people of Karang Anyar village, Ketapang sub-district, and Sampan regency. This research uses a qualitative approach, with data collection techniques using documentation, observation, and interview techniques. Meanwhile, checking the validity of the data is obtained through extending observations, increasing persistence in research, and triangulation. The research's findings lead the researcher to the following conclusions: first, Totoh ginger coffee owners have adopted the marketing mix concept, which consists of the 4Ps: product strategy (product), price strategy (price), distribution location strategy (place), and promotion strategy (promotion), as their development strategy to boost sales and keep customers. In its marketing strategy, the owner of Totoh ginger coffee applies a strategy that is in accordance with Islamic business ethics, namely: Al-insaniyah, or humanity; akhlakul karimah, in accordance with customer wishes; listening to customer criticism and suggestions; honesty; being realistic (not making things up); respecting customers; offering quality and halal goods; and offering products that do not harm customers. Second, the strategy implemented in the production process, price, location, and promotion is that there are no deviations made by Totoh ginger coffee product business actors, whether in the supply of raw materials, the manufacturing process, or the sales process. The Totoh ginger coffee business has implemented Islamic economic principles, namely Tawheed; whatever is done is based on the existence of Allah SWT Khilafah and Al-Ta'awanun, namely mutual help. The raw materials used are natural and halal materials, which are permitted in Islam, are obtained in a good way, and are sold only through orders from consumers via social media.